Application of supercritical fluid extraction for extraction or enrichment of phospholipids in egg and dairy products: A review. (29th March 2021) - Krishnegowda, Rajesh; Ravindra, Menon Rekha; Sharma, Monika
Abstract : Phospholipids (PLs) are polar lipids that are found in dairy products, egg, and oilseeds. They are amphiphilic in nature and find application in many foods as a functional ingredient. As PLs are distributed in food matrix in dilute form, attempts to concentrate the same by adopting suitable technical interventions have been widely investigated. One of the more successful approaches that have been reported is the application of supercritical fluid extraction (SCFE) to extract PLs using suitable cosolvents. The extraction protocol to extract PLs from dairy products and eggs using SCFE also includes a two‐step process, namely, separation of neutral lipids using neat CO2 followed by subsequent separation of polar lipids from the residue using cosolvent and CO2 . This review is an attempt to compile information on dairy and egg PLs extracted using SCFE under varied operational factors. It is expected that the compilation will serve as resource for investigators working in this research area. Practical Applications: Milk fat processing results in valuable by‐products which can be suitably volarized to increase profitability through processing gains and reduce environmental footprints in dairy industry. The by‐products such as buttermilk, butter serum, ghee residue, and so forth can be tapped as potential sources for phospholipid (PL). Eggs have already been recognized as a good source of PLs, which are reported to have preventive effect on pathogens, cancer protective, anti‐inflammation and cardiovascular disease. Two challenges could be anticipated in the fractionation of PLs from egg and milk by‐products. First, extraction of lipids from substrate which include polar and neutral lipids. Second, separation of neutral and polar lipids from the lipid extract. Conventional methods of extraction involve many solvents for the wide range of lipids to be extracted, which often result in incomplete extraction. Supercritical fluid extraction (SCFE) technique is reported to be useful in extraction and separation of PLs from dairy and egg products. Process intervention strategies and optimization approaches have been undertaken by various researchers to quantify and improve extractability of PLs using SCFE. The paper is a compilation of the scientific information related to extraction of dairy and egg PLs using SCFE, which will serve as a knowledge resource for researchers working in related fields. Abstract : Supercritical fluid extraction approach was used to extract phospholipids from egg and dairy products. In the process of extraction, neat CO2 was used as solvent to extract nonpolar lipids (neutral lipids) as first step. Subsequently, some cosolvents with CO2 resulted in separation of phospholipids from food matrix.